'Comments in Tags, Please!': Tagging practices on Tumblr. (April 2018) - Bourlai, Elli E.
Highlights: Comment tags are more popular among fandoms. They are longer than keyword tags and have higher presence of special characters. Comment tags have 3 main discourse functions: opinion, reaction, aside. Reaction is the most popular discourse function of comment tags. Both social structure and technological design influence social tagging in Tumblr. Abstract: Tumblr is one of the most popular content sharing websites, where the use of keyword tags that enhance the searchability and visibility of posts is prominent. However, this resource has been creatively exploited by some users beyond its folksonomic use: Since Tumblr does not have a separate comment section for posts, the tag section may also be used for tags with discourse functions such as expressing an opinion, a reaction, or including asides. This article explores the practice of including comments in tags, taking into account the specific technological features of Tumblr's tagging system, as well as the role of the communities within the website. The corpus analyzed in the study comprises two datasets collected from the general 'Trending' page of Tumblr and 60 fan communities ('fandoms'). Comment tags and their identified discourse functions (opinion, reaction, aside) are analyzed quantitatively for differences regarding use, structure, and sentiment. The analysis shows significant differences between the comment tags and traditional keyword tags, as well as among comment tags with the three different discourse functions. The results suggest that social tagging practices on Tumblr are influenced both by the technological specifications of the platform and the social structure of the website.